The Filipino family in crisis ten case studies - Jamias, Eugenia C.; Serafica, Felicisima; Varias, Rodolfo R.; Philippines (Republic) Department of Social Welfare; Unicef-Assisted Social Services Project (Manila Social Welfare Administration, Unicef-Assisted Social Services Project)
"These case studies seek to delve more deeply into the dynamics of the Filipino and his family. Through depth studies of ten patients, this casebook will explore the symptomatology, psychopathology, and the corresponding socio-cultural determinants. The project grew out of the questions raised during clinical case conferences and informal discussions among members of the team. Its objectives are: (1) To bring to light psychoanalytic theory as reflected in the clinical problems of Filipino patient. (2) To discuss in the clinical context Filipino values as they can be related to personality development. (3) To illustrate the diagnostic study of an individual using the team approach. (4) To provide a casebook for the use to students in psychiatry, psychology, social work and other related disciplines."--P. vii.
Introduction -- Chapter I. The structure of personality -- Chapter II. Psychopathology -- Chapter III. "A world of his own" -- Chapter IV. "Not a question of ability" -- Chapter V. "A phase to outgrow" -- Chapter VI. "Empty inside" -- Chapter VII. "Daddy's girl" -- Chapter VIII. "The secret alphabet" -- Chapter IX. "No cause for trouble" -- Chapter X. "Peace at any cost" -- Chapter XI. "A small town man headed for the big time, but never getting there" -- Chapter XII. "I am wallowing in my own depression" -- Chapter XIII. Conclusion.
Keywords: Family -- Philippines -- Case studies; Family psychotherapy -- Cases, clinical reports